Leksem Aktivitas Tangan Menyakiti dalam Bahasa Jawa Dialek Desa Malangsuko Kecamatan Tumpang Kabupaten Malang - Utami, Sri (FKIP Universitas Wisnuwardhana, 2023)
This research aims to describe lexemes that refer to the activity of hurting hands in the Javanese language of Malangsuko village, Tumpang District, Malang Regency. The data in this paper are in the form of lexemes that refer to hand activities. This research is a type of qualitative descriptive research using research methods (Introspective), self-dreaming and interviews. The steps taken are 1) describing the activity of hurting hands in the Javanese language of Malangsuko village 2) describing the meaning components of each lexeme 3) see the same components in each lexeme 4) create a differentiation matrix for each lexeme 5) describe the status of the semantic features in the matrix with the symbols -, 0, and +. 6) conclude with a diagram based on the meaning component analysis that has been carried out. The results of the research show that